Outcome of management of congenital diaphragmatic hernia - Saha, Amar Kumar; Ali, Md Barkat; Biswas, Sunil Kumar (Bangladesh Medical Journal Khulna, 2015)
Congenital Diaphragmatic Hernia (CDH) is a defect in the dome of diaphragm, more often in left and postero-lateral that permits the herniation of abdominal contents into the thorax. The lungs hypoplasia, pulmonary hypertension and persistent foetal circulation are important determinant of survival. The incidence is <5 in 10,000 live-births. Antenatal diagnosis is ofen made and this may be helpful in postnatal management. Treatment after birth requires all the refinements of critical care prior to surgical correction. The best hospital series report 80-100% survival. Advances in surgical management include delayed surgical approach that enables preoperative stabilization, improved prenatal diagnosis, introduction of minimal invasive surgery and application of extracorporeal membrane oxygenation in addition to the standard open repair. In our short series survival was 100% where surgical correction was made on selective 12 cases of left sided CDH in a non-ICU set-up. DOI: http://dx.doi.org/10.3329/bmjk.v47i1-2.22556 Bang Med J (Khulna) 2014; 47 : 12-15